Optimization Analysis of Protection Coordination in Loop Distribution Systems with Integrated Distributed Generation Using the Firefly Algorithm and Conventional Methods - Lestari, Destina Surya; Nursita, Ersalia Dewi; Wijanarko, Rahmat Febrianto (Universitas Pendidikan Nasional, 2025)
This study evaluates the comparison between conventional methods and the firefly method in the protection coordination of power systems with the addition of Distributed Generators (DG). DG is a crucial component in modern systems that can influence the performance of protection and existing protection coordination. Conventional methods involve relay setting adjustments and fault current coordination, but the addition of DG can significantly alter system characteristics, affecting the performance of conventional methods. This study introduces the firefly method, which utilizes an optimization algorithm inspired by the light-emitting behavior of fireflies to dynamically adjust relay settings, considering system changes due to the addition of DG. The results indicate that the firefly method enhances protection coordination performance by being more adaptive to system changes. Compared to conventional methods, the firefly method provides better responsiveness to dynamic variations in power flow and fault currents. Thus, this study concludes that implementing the firefly method in power system protection coordination with DG integration can improve system reliability and the overall efficiency of DG utilization. This method offers a more adaptive and responsive solution to changes in modern power systems.